Hide and seek - Shipton, Paul. (London : Macmillan education, 2011)
This is a six-level series of readers for children learning english, bringing together a variety of enjoyable fiction and non-fiction titles. This series provides reinforcement of the basic structures and vocabulary contained in most major primary courses.
Includes activities and a picture dictionary.
Keywords: Juvenile literature; Readers (Primary); English language -- Study and teaching (Primary); Children's books